Chromatin-informed inference of transcriptional programs in gynecologic and basal breast cancers - Hatice U. Osmanbeyoglu (Nature Portfolio, 2019)
Epigenomic data on chromatin accessibility and transcription factor occupancy can reveal enhancer landscapes in cancer. Here, the authors develop a computational strategy called PSIONIC (patient-specific inference of networks informed by chromatin) to model the impact of enhancers on transcriptional programs in gynecologic and basal breast cancers.